Evaluation of assays for nucleic acid testing for the prevention of chikungunya and dengue virus transmission by blood transfusion - Gallian, Pierre; Dupont, Isabelle; Lacoste, Marjorie; Brisbarre, Nadège; Isnard, Christine; Delouane, Idriss; Richard, Pascale; Morel, Pascal; Laperche, Syria; Lamballerie, Xavier (Transfusion (Philadelphia, Pa.), 2024)
Background The large dengue (DENV) and chikungunya (CHIKV) outbreaks observed during the last decade across the world, as well as local transmissions in non‐endemic areas are a growing concern for blood safety. The aim of this study was to evaluate and compare the sensitivity of nucleic acid tests (NAT) detecting DENV and CHIKV RNA. Materials and Methods Using DENV 1 to 4 International Standards, the limits of detection (LODs) calculated by probit analysis of two NAT assays; the cobas CHIKV/DENV assay (Roche Diagnostics) and the Procleix Dengue Virus Assay (Grifols) were compared. In addition, CHIKV‐RNA LOD of the cobas CHIKV/DENV assay was evaluated. Results For dengue, the 95% LOD of the cobas assay ranged between 4.10 [CI95%: 2.70–8.19] IU/mL (DENV‐2) and 7.07 [CI95%: 4.34–14.89] IU/mL (DENV‐4), and between 2.19 [CI95%: 1.53–3.83] IU/mL (DENV‐3) and 5.84 [CI95%: 3.84–10.77] IU/mL (DENV‐1) for Procleix assay. The Procleix assay had a significant lower LOD for DENV‐3 (2.19 vs. 5.89 IU/mL) when compared to the cobas assay (p = 0.005). The 95% LOD for CHIKV‐RNA detection of the cobas assay was 4.76 [CI95%: 3.08–8.94] IU/mL. Discussion The two NAT assays developed for blood donor screening evaluated in this study demonstrated high and similar analytical performance. Subject to an appropriate risk‐benefit assessment, they can be used to support blood safety during outbreaks in endemic areas or in non‐endemic areas as an alternative to deferring blood donors during local transmission likely to affect the blood supply. The development of multiplex assays is expected to optimize laboratory organization.